(untitled) (Iter, 2022)
“ Echoes of Italy in the chilean letters ” intends to check the presence ofilatian writers or some of their descendants, as well as the influences of some aspects of the italian letters in chilean literary history. To that end, national works are revised, starting with La Araucana up to the current narrative and poetry, specially the one that ineludes somefeatures takenfrom the great ancient Román authors or outstanding italian writers. Finally, a summary ofthe literary activity of italian authors who Uve in Chile or their descendants is submmitted to the readers.